2009
DOI: 10.1364/ao.48.002255
|View full text |Cite
|
Sign up to set email alerts
|

Silver-doped photopolymer media for holographic recording

Abstract: Incorporation of silver ions into a dye-sensitized poly(vinyl alcohol)/acrylamide photopolymer is observed to give better performance compared to other metal-ion-doped photopolymer holographic recording media. Plane-wave transmission gratings were recorded in the photopolymer films using a He-Ne laser, and various holographic parameters were optimized so as to explore maximum potential of the material for various holographic applications. Silver-doped films showed good energy sensitivity, and gratings recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…Ио-ны Ag + , используемые в качестве сшивающего ре-агента, позволяют регистрировать пропускающие го-лограммы высокого качества в реальном времени в ПВА/акриламидной композиции [72]. Для регистрации голограмм с ДЭ= 70% энергетические затраты излуче-ния гелий-неонового лазера составляли 10 mJ/cm 2 [73].…”
Section: O O Ohunclassified
“…Ио-ны Ag + , используемые в качестве сшивающего ре-агента, позволяют регистрировать пропускающие го-лограммы высокого качества в реальном времени в ПВА/акриламидной композиции [72]. Для регистрации голограмм с ДЭ= 70% энергетические затраты излуче-ния гелий-неонового лазера составляли 10 mJ/cm 2 [73].…”
Section: O O Ohunclassified
“…To date, polymeric materials, such as poly(methyl methacrylate), poly(vinyl alcohol) (PVA), and others, have been widely investigated for holographic applications [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript presents an investigation of the optical and electrical properties of FeCl 3 -PVA samples with varied concentrations of FeCl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously our research group has successfully recorded holographic gratings in acrylamide incorporated poly (vinyl alcohol) film with a diffraction efficiency (DE) of 70% with an exposure energy of 125 mJ/cm 2 , having a dye concentration of 2.09 Â 10 À4 M, but a gradual decrease in diffraction efficiency was observed on storage. 9 The reason for the decrease may be due to the diffusion of residual dye molecules from destructive region to constructive region and by the instability of leuco form of the dye molecule. 8 Doping with ammonium dichromate and copper chloride, resulted in good storage life with low diffraction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…But Pramitha et al has reported that by using silver ion as a crosslinker, a diffraction efficiency of 75% could be achieved with an exposure energy of 80 mJ/cm 2 and it remained as 50% even after 1 year. 9 In order to study the storage life of the material in the absence of metal ions, the dye concentration was reduced from 2.09 Â 10 À4 M and concentration was optimized by recording gratings at different exposure energies. Surprisingly, good diffraction efficiency and storage life was obtained for a dye concentration of 1.4 Â 10 À4 M. From this result, the role of dye molecules on the material's storage life was clear.…”
Section: Introductionmentioning
confidence: 99%